urgent

Asked by 2806rahul | 16th May, 2010, 08:50: PM

Expert Answer:

cot θ - cot3θ = 1/tan θ - 1/tan3θ = (tan3θ - tanθ)/tanθ tan3θ       .......(1)

Now,

[cot θ/(cot θ - cot3θ)] + [tan θ/(tan θ - tan3θ)] =

Using (1) to replace the denominator in first term,

[tanθ tan3θcot θ/((tan3θ - tanθ)] + [tan θ/(tan θ - tan3θ)] =

[tan3θ/((tan3θ - tanθ)] + [tan θ/(tan θ - tan3θ)] =                         ... tanθ cotθ = 1

[- tan3θ/((tanθ - tan3θ)] + [tan θ/(tan θ - tan3θ)] =

(tan θ - tan3θ)/(tan θ - tan3θ) = 1

Regards,

Team,

TopperLearning.

Answered by  | 17th May, 2010, 07:11: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.